Antiproliferative Activity of Aqueous Leaf Extract of Annona muricata L. on the Prostate, BPH-1 Cells, and Some Target Genes. (January 2015) - Asare, George Awuku; Afriyie, Dan; Ngala, Robert A.; Abutiate, Harry; Doku, Derek; Mahmood, Seidu A.; Rahman, Habibur
Background. Annona muricata L. has been reported to possess antitumor and antiproliferative properties. Not much work has been done on its effect on BPH-1 cell lines, and no in vivo studies targeting the prostate organ exist. The study determined the effect of A muricata on human BPH-1 cells and prostate organ. Methods . The MTT assay was performed on BPH-1 cells using the aqueous leaf extract of A muricata . Cells (1 × 10 5 per well) were challenged with 0.5, 1.0, and 1.5 mg/mL extract for 24, 48, and 72 hours. Cell proliferation and morphology were examined microscopically. BPH-1 cells (1 × 10 4 per well) were seeded into 6-well plates and incubated for 48 hours with 0.5, 1.0, and 1.5 mg/mL A muricata extract. Reverse transcriptase polymerase chain reaction was performed using mRNA extracted from the cells. Possible target genes, Bax and Bcl-2, were examined. Twenty F344 male rats (≈200 g) were gavaged 30 mg/mL (10 rats) and 300 mg/mL (10 rats) and fed ad libitum alongside 10 control rats. Rats were sacrificed after 60 days. The prostate, seminal vesicles, and testes were harvested for histological examination. Results. Annona muricata demonstrated antiproliferative effects with an IC50 of 1.36 mg/mL. Best results were obtained after 48 hours, with near cell extinction at 72 hours. Bax gene was upregulated, while Bcl-2 was downregulated. Normal histological architecture was observed for all testes. Seminal vesicle was significantly reduced in test groups ( P < .05) and demonstrated marked atrophy with increased cellularity and the acinii, empty of secretion. Prostate of test groups were reduced with epithelial lining showing pyknotic nucleus, condensation, and marginalization of the nuclear material, characteristic of apoptosis of the glandular epithelium. Furthermore, scanty prostatic secretion with flattening of acinar epithelial lining occurred. Conclusion. Annona muricata has antiproliferative effects on BPH-1 cells and reduces prostate size, possibly through apoptosis.